Environmental Enrichment and Aerobic Exercise Enhances Spatial Memory and Synaptophysin Expression in Rats - Diah Ayu Aguspa Dita; Nurul Paramita; Ria Kodariah; Neng Tine Kartinah (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Exposure to environmental enrichment has a positive effect on brain function, including improved cognition. Environmental enrichment has many aspects, including social interactions, object stimulations, and physical activities. Exercise and environmental enrichment can be considered to improve cognitive function with different underlying mechanisms. This study aims to compare the effects of environmental enrichment and aerobic exercise at both synaptic and whole-organism levels using synapyophysin as a measure of synaptic physiology and spatial memory as a measure of cognitive function.METHODS: A six-week in vivo experimental study on 15, 6-month old male Wistar rats randomly divided into three groups (n=5): aerobic group (A), enriched environment group (EE), and enriched with an aerobic or combined group (EEA). All rats were tested four times in the Water-E maze (WEM) task at weeks 0, 2, 4, and 6 of the study. We used immunohistochemistry to determine the synaptophysin expression in hippocampal CA1 region.RESULTS: Based on synaptophysin immunostaining, there were higher optical density scores for synaptophysin in hippocampal CA1 region following EEA, but there were no statistically significant differences between groups (ANOVA test, p>0.05). The spatial memory test showed there were significantly reduced travel time and total errors from the 2nd and 4th weeks in the EEA group, respectively (p<0.05).CONCLUSION: The combination of enriched environment and aerobic exercise seems to rapidly improve spatial memory and enhances the presynaptic protein, synaptophysin in hippocampal CA1 region.KEYWORDS: aerobic exercise, environmental enrichment, spatial memory, synaptophysin, Water-E maze